Effects of Coconut Water, Glycerol, and Storage Temperature on the Viability of Catfish (Clarias sp.) Sperm - Putri, Restu Gusmanda; Atifah, Yusni; Ahda, Yuni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The high production of catfish (Clarias sp.) requires a sustainable seed supply, which is frequently constrained by the asynchronous gonad maturity of broodstock. Sperm preservation using young coconut water as a natural extender and glycerol as a cryoprotectant offers a viable solution to address this limitation. This study aimed to analyze the interactive effects of extender formulations and storage temperatures on the viability of catfish spermatozoa after four days of preservation. Semen was extracted by stripping from a single mature male broodstock weighing 3,000 g. The experiment employed a two-factor factorial Completely Randomized Design (CRD). A total of 30 experimental units consisting of 0.2 mL microtubes were used, including 27 units for the factorial treatment combinations and 3 unreplicated control units (100% young coconut water), with one control assigned to each storage temperature. The factorial treatments consisted of two factors with three replications: extender formulation (P1: 75% young coconut water + 25% glycerol; P2: 50% young coconut water + 50% glycerol; and P3: 25% young coconut water + 75% glycerol) and storage temperature (27°C, 5°C, and −20°C). Sperm viability was evaluated using 1% eosin staining and analyzed by two-way ANOVA (α = 0.05). The results showed that storage at 27°C and −20°C caused complete spermatozoa mortality (0% viability) across all extender treatments and the control. In contrast, storage at 5°C produced the highest sperm viability in treatment P1 (82.88%), followed by P2 (65.38%), while P3 and the control exhibited 0% viability. In conclusion, the combination of young coconut water and glycerol stored at 5°C effectively maintained the viability of catfish spermatozoa, with the formulation containing 25% glycerol (P1) identified as the optimum treatment for short-term preservation.